Reconciling use-based and Registration-Based Rights within the Trade Mark System: What the Problems with Section 58A of the Trade Marks Act Tell Us. (March 2014) - Handler, Michael; Burrell, Robert
Reconciling registration and use as mechanisms by which rights can be acquired in a trade mark is inherently difficult. The federal Australian registered trade mark system is built around a hybrid of a registration-based and a use-based model of protection. While it is perfectly possible to defend such a dual model, the two means of acquiring trade mark rights rest on very different logics. In the event of a conflict between a registered mark and a mark that has been used for some time the question of which should take precedence is not necessarily capable of being determined a priori. The relationship between registration and use is mediated by a number of provisions of the Trade Marks Act 1995 (Cth). In this article we focus on one such provision, s 58A, a relatively recent addition to the legal landscape. Through a close analysis of s 58A, focusing on court decisions and decisions of the Trade Marks Office that have applied this provision, we demonstrate that s 58A has the potential to operate in an entirely unsatisfactory manner. We then use problems with s 58A as a vehicle to explore the relationship between use-based and registration-based rights generally, suggesting a new conceptual framework that might serve to guide future discussion of how the relationship between registration and use ought to be mediated.